USING VIRTUAL REALITY TO THE SAFETY WARNINGS DESIGN: THE EFFICIENCY THROUGH PRESENCE - Schiavini, Reginaldo; Meurer, Heli (Revista Conhecimento Online: Diversidade e Inclusão Social, 2021)
The objective of this study was to use virtual reality as a validation method of a new multimodal warning for use in situations of risk and danger. This warning is intended to be more efficient than the static warnings as regards their ability to convey clear, objective information and securely. The virtual environment used was developed with immersive virtual reality simulating a risk and danger to the user. This virtual environment allows situations are simulated in real life would be impossible for putting at risk the lives of people. For the warning efficiency were evaluated, we used two warnings, static and multimodal, which consisted of harmonization between the ISO and ANSI standards. As innovation factor used was the explanation of the consequences of non-compliance. Multimodal elements used in the notice were a file with a recorded human voice and a flashing red light. These results demonstrated that the virtual environment used, and the multimodal warning were efficient in their goals. The results of the variables used were positive and the hypotheses was validated with the use of statistical tests.